Perancangan Sistem Informasi Pemesanan Pada Onoy Cakes Bakery Terintegrasi Multi-Kios Berbasis Android - Febri; Sunoto, Akwan (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2026)
The rapid development of information technology requires companies to adapt in order to improve operational efficiency, including in the field of product ordering. Onoy, a bakery with several outlets in Jambi City, still relies on a manual ordering and recording system, which often leads to discrepancies in orders, difficulties in stock monitoring, and delays in fulfilling customer requests. This study aims to design and develop an Android-based bread ordering information system integrated across multiple kiosks, with a focus on analyzing the highest orders as a basis for production decision-making. The software development method used is the waterfall model, which includes requirements analysis, system design, implementation, testing, and documentation. The results of this research produced an ordering application capable of handling bread orders, selecting product types and quantities, viewing order data, managing reports, and facilitating user data management. This system helps outlets reduce ordering errors, improve data accuracy, speed up transactions, and support managerial decision-making regarding production quantities based on the highest demand. Therefore, the system is expected to enhance Onoy operational effectiveness and provide better services to customer.